ANALISIS KEBUTUHAN PENGGUNAAN MEDIA PEMBELAJARAN IPA BERBASIS TEKNOLOGI DI ERA MERDEKA BELAJAR - Riska Putri Taupik; Firman; Desyandri (STKIP Subang, 2022)
The implementation of an independent curriculum requires teachers to remain creative and innovative in creating the best learning for their students, even though they are still in a condition of adjusting to new things. The rapid development of technology towards the industrial revolution 5.0 makes it easy for teachers to create effective and efficient learning media. This study aims to analyze the learning media needed in science learning in the independent era of learning at the elementary school level. The population of this study was Cluster II Koto Salak, and the research sample was elementary school A students with a total of 150 high school students and three high class teachers. The research method used by researchers is qualitative. Data collection techniques used are observation and interviews. Data analysis uses an interactive analysis model. The results of this study indicate that the use of technology-based science learning media is urgently needed, both for educators and students. The use of technology-based learning media can provide convenience for educators in creating interactive, student-centered learning, developing students' critical thinking skills, and providing meaningful learning and in accordance with the child's character.